Engel's Law Reconsidered - Manisha Chakrabarty; Werner Hildenbrand (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
Engel's verbal formulation of his Law expresses a "negativ stochastic association" of the bivariate distribution of income and food share across the population. Among the many different definitions of association four are chosen: Kendall's tau, negative quadrant dependence, stochastically decreasing conditional food share distribution functions, and decreasing regression. To link Engel's Law with individual behavior a decreasing regression is not sufficient, the stronger notion of associations are needed. This motivates the empirical analysis of section 4. It is shown that the above notions of associations are well supported by empirical evidence.
Keywords: B10; B21; B23; 330; Engel's Law; non- parametric regression; Kendall's tau; stochastic dominance; Mikroökonomische Konsumfunktion; Nahrungsmittelkonsum; Verbraucherausgaben; Theorie; Schätzung; Indien